Inserção profissional em “escola de passagem” na visão de professores iniciantes e profissional gestor de uma CEI do município de São Paulo - Oliveira, Regina Célia Tolentino (2020)
This research work aims to investigate the relations between the school administration and the several types of beginning teachers such as: beginners in the career (newly graduated), in the school level of the Early Childhood Education (migrated from other school level) and/or beginners in the school unity chosen in a school of passage, integrating the studies and research works with the institution reality. This work is considered qualitative research, accomplished by means of documental analysis of the following: the Minute Book, Special Project of Action 2019 (PEA), records of teachers who participated in PEA (Special Project of Action 2019), and Pedagogic References and Guidelines (ROP) of the institution, besides applying a questionnaire to 16 beginning teachers and interviews with the coordinator of the institution. This research work aimed to answer the following questions: How does the school environment, without the presence of experience teachers, modify the condition of profession insertion of the beginning teachers? Which implications does it bring to the professionals of the school administration? How do they conduct the inclusion of these beginners in the school unity? How does the beginning teachers’ commitment happen in this institution and which were the beginning teachers’ educational aspirations when they arrived at the institution? Theoretical support for this research work is provided by authors such as: Marcelo, with the concept of teacher’s professional development, and Vaillant, with the evidences that the social and cultural environment of the institution directly influences the promotion or inhibition of the teacher’s professional development; Huberman, Ferreirinho and Guarnieri, with the concept of teacher’s professional life cycle and characterization of the teacher in the beginning of the career; and Giovanni, Knoblauch and Franca, with the concept of school of passage. The data obtained, organized in charts and tables, confirm in part the guiding hypothesis of the research, that beginning teachers have difficulty in assuming the specific role of teachers of babies and young children, within the context of a specific school with characteristics of “passing school”, where babies and young children are placed on a “forgetfulness” plan in the face of so many other anxieties and concerns, and that these first years of professional activity are not always a smooth process, especially if this professional insertion does not count on specific support (presence of experienced colleagues and actions of the management team)